Uganda Systematic Country Diagnostic Update - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2021)
Since the 2015 SCD, some economic progress had been shared and progress in poverty reduction was achieved, but the COVID-19 crisis has in part reversed these developments. Uganda’s broad development narrative has not changed significantly since the 2015 SCD, with the COVID-19 crisis further aggravating the existing challenges. Improvements in economic developments have slowed over the past five years compared to peers, with a particularly sharp deceleration in real per capita GDP growth. Addressing the inequality of opportunities, which is pervasive in Uganda, is key for the postCOVID recovery. The SCD Update revisits the priority areas and actions for Uganda today, based on the latest developments and analysis of constraints.